Aktifitas Produksi dalam Perspektif Ekonomi Islam - Mujahidin, Akhmad (ISLAMICA: Jurnal Studi Keislaman, 2009)
Economic activities contain three parts, namely production, distribution, and consumption. This paper deals with the first one in the perspective of Islam. We maintain that at no point in human history was there any economic system that could successfully achieve an absolute happiness and wellbeing for human kind. Islamic system of economics included. Nonetheless, we argue that Islam consists of values and norms that may lead toward that end if they are properly and appropriately understood and applied. We do not find in Islam what we found in the conventional economic system where there are rooms for committing corruption and manipulation. For Islam, economic activities as far as production is concerned must be directed toward achieving the goodness and prosperity of all human kind, and not toward enriching certain individuals and groups among individuals.